2018
DOI: 10.5194/acp-18-4639-2018
|View full text |Cite
|
Sign up to set email alerts
|

Sources and physicochemical characteristics of black carbon aerosol from the southeastern Tibetan Plateau: internal mixing enhances light absorption

Abstract: Abstract. Black carbon (BC) aerosol has important effects on the climate and hydrology of the Tibetan Plateau (TP). An intensive measurement campaign was conducted at Lulang (∼ 3300 m a.s.l. – above sea level), southeastern TP, from September to October 2015, to investigate the sources and physicochemical characteristics of refractory BC (rBC) aerosol. The average rBC mass concentration was 0.31 ± 0.55 µg m−3, which is higher than most prior results for BC on the TP. A clear diurnal cycle in rBC showed high va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 76 publications
(99 reference statements)
3
41
1
Order By: Relevance
“…The high BC scavenging ratios at this station could also be explained by the aging of aerosols during the longrange transport from South Asia (Li, Bosch, et al, 2016;Lüthi et al, 2015;Yang et al, 2018). The scavenging ratios for both WIOC and BC at the Lulang and Everest stations were relatively low compared to those at Nam Co Station because the atmospheric concentrations of WIOC and BC at the former two stations were much higher than those at Nam Co Station (Table S2) due to the large influence of local emissions Wang et al, 2018). In contrast, the concentrations of WIOC and BC in precipitation at these two stations were slightly higher than or comparable to those at Nam Co Station (Table 1).…”
Section: Scavenging Ratios Of Wioc and Bcmentioning
confidence: 89%
“…The high BC scavenging ratios at this station could also be explained by the aging of aerosols during the longrange transport from South Asia (Li, Bosch, et al, 2016;Lüthi et al, 2015;Yang et al, 2018). The scavenging ratios for both WIOC and BC at the Lulang and Everest stations were relatively low compared to those at Nam Co Station because the atmospheric concentrations of WIOC and BC at the former two stations were much higher than those at Nam Co Station (Table S2) due to the large influence of local emissions Wang et al, 2018). In contrast, the concentrations of WIOC and BC in precipitation at these two stations were slightly higher than or comparable to those at Nam Co Station (Table 1).…”
Section: Scavenging Ratios Of Wioc and Bcmentioning
confidence: 89%
“…3.3 BC/PM 2.5 and BC/CO ratios BC/PM 2.5 and BC/CO ratios are widely used to identify the sources of BC Wang et al, 2011;Verma et al, 2010;Chow et al, 2011). Generally, ratios of BC/PM 2.5 from mobile sources (0.059-0.74) and area sources (0.032-0.33) are higher than those from industrial sources (0.0046-0.03).…”
Section: Figures 6 and S7mentioning
confidence: 99%
“…Absence of day time enhancement of nitrate and ammonium indicated that photochemical production may not be significant or possibly destruction (evaporative loss, i.e., Even though it is very difficult to determine the coating material on the BC particles that exist in a multi-component organic, inorganic aerosols, gaseous vapours system, the above discussion suggests two contrasting possibilities of coating material on BC: (a) concurrent peaks in RCT (as seen in Figure 8) and sulphate during the diurnal cycles indicates that the most probable material for the coating is sulphate, whereas (b) possibility of organic matter acting as coating material cannot be ruled out because observed minima in the mass fraction of organics during RCT peaks (during dawn and afternoon 5 hours) suggested a possible loss of organic vapours through condensation on large number of pre-existing BC particles, thereby contributing to their coating. Boundary layer dynamics and source processes play an important role not only on particle loading but also in determining the coating Gong et al, 2016;Thamban et al, 2017;Wang et al, 2018). Increased ventilation during day time due to enhanced boundary layer heights dilutes aerosol concentrations, thereby reduces competition among particles for adsorption of condensable vapours.…”
Section: Diurnal Variations Of Nr-pm1 Species and Association With Bcmentioning
confidence: 99%
“…A summary of MMD values reported in the literature with different emission sources and atmospheric conditions along with the present values is made in Table-3. Several earlier publications reported a range of MMD values (0.100-0.170 µm) for 30 urban regions with near source fossil fuel emissions (McMeeking et al, 2010;Liu et al, 2014;Laborde et al, 2013;Cappa et al, 2012;Kondo et al, 2011;Cheng et al, 2018), whereas, urban/continental outflows depict MMDs in the range of 0.140-0.180 µm (Shiraiwa et al, 2007;Wang et al, 2018). The MMD values are ~0.211 ± 0.014 µm for fresh biofuel/crop residue sources (Raatikainen et al, 2017), and in the range ~0.220-0.240 µm for aged BC from biomass burning sources (Liu et al,. https://doi.org /10.5194/acp-2019-376 Preprint.…”
mentioning
confidence: 99%